2013
DOI: 10.1021/ef400386j
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Copper in Ash from a Fluidized-Bed Boiler Fired with Municipal Solid Waste

Abstract: Copper is one of the most important trace elements in municipal solid waste (MSW) combustion. Knowledge of the speciation of copper is fundamental for the understanding of the effects of copper compounds on the combustion chemistry, the evaluation of the environmental effects of copper in ash leachates, and the development of methods to recover copper from the MSW combustion ash. In this work, an investigation of the speciation of copper in four ash flows from a bubbling fluidizedbed boiler using synchrotron-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…The CuCr 2 O 4 , as well as CuO and metallic Cu, have all been identified in other ash fractions (e.g. bottom bed ash) from the same boiler and on the same occasion (Lassesson et al, 2013). Metallic copper pieces may have been covered by glass melt in the combustion bed.…”
Section: Figurementioning
confidence: 93%
See 1 more Smart Citation
“…The CuCr 2 O 4 , as well as CuO and metallic Cu, have all been identified in other ash fractions (e.g. bottom bed ash) from the same boiler and on the same occasion (Lassesson et al, 2013). Metallic copper pieces may have been covered by glass melt in the combustion bed.…”
Section: Figurementioning
confidence: 93%
“…An investigation of the copper speciation in the different ash flows from a bubbling fluidized bed boiler fired with MSW using XAS methods has recently been carried out by Lassesson and coworkers (Lassesson and Steenari, 2013). The results showed that copper occurred mainly as copper metal, copper oxides (CuO and Cu 2 O) and mixed oxides (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that Cr existed inside the structure of the matrix particles (some Cr also found in micro wood pieces in ash), while Cu in addition to these places, was also was found condensed on surface of coarser ash particles and As was found associated with Ca in the ash. Similarly, Lassesson and Steenari [15] investigated Cu association in MSWI bottom ash using X-ray absorption spectrometry and X-ray diffraction (XRD/XAS) and reported that it was a mixture of Cu(0), Cu(I), and Cu(II) in the relative concentrations of 10-20% Cu(0), 25-35% Cu(I), and 55-65% Cu(II) and were most likely oxides (Cu 2 O, CuO, CuCr 2 O 4 ).…”
Section: Introductionmentioning
confidence: 91%
“…These crystal species correspond to the common diffraction peaks of the MSWIs ash spectrum. [27,32] In addition, aluminium silicon oxides and copper oxides were detected in MB-BA, and iron oxides …”
Section: Total Characterization Of the Ashesmentioning
confidence: 99%